Design, Synthesis, and Biological Evaluation of Tryptanthrin Alkaloids as Potential anti-Diabetic and Anticancer Agents. (2nd January 2023) - Teja, Chitrala; Ramanathan, Karuppasamy; Naresh, Kondapalli; Vidya, R.; Gomathi, K.; Nawaz, Fazlur Rahman
Abstract: An efficient green chemical approach has been reported to synthesize tryptanthrin alkaloids, utilizing isatin and isatoic anhydride as a substrate in the presence of tetrabutylammonium salt-based ionic liquids (TBA-ILs) as catalyst and reaction medium under microwave conditions (MWs). The reaction proceeds evenly under mild conditions to provide the bioactive natural product tryptanthrins in excellent yields. Besides, the molecular docking studies show that all the synthesized scaffolds exhibit potential binding affinities toward α-amylase, α-glucosidase ligands, GLP-1, and EGFR receptors; the in-vitro α-amylase and α-glucosidase assays show positive inhibition. In addition, the in vitro anticancer activity against A-549 non-small lung cancer (NSLC) cell lines leads to excellent inhibition. The present findings show the therapeutic potential of the tryptanthrins for targeting antidiabetic and anticancer activities.